Local Self-Governance and Varieties of Statehood Tensions and Cooperation - Neubert, Dieter; Lauth, Hans-Joachim; Mohamad-Klotzbach, Christoph (Contributions to Political Science, 2022)
VIII, 198 p. 5 illus., 2 illus. in color.